Hazard assessment of storm events in the central region of the Portuguese coast - Carmo, José S. A. (2014)
The environmental and socio-economic importance of the coastal areas is widely recognized, but these areas face today severe weaknesses and high-risk situations. The increased demand and human occupation of the coast has greatly contributed to increase such weaknesses. Today, throughout the world, in all countries with coastlines, episodes of waves overtopping and coastal flooding are frequent. These episodes are usually responsible for property losses and often put human lives at risk. The floods are caused by coastal storms due to the action of very strong winds. The propagation of these storms towards the coast induces high water levels. Consequently, carrying out series of storm scenarios and analyzing their impacts through numerical modelling is of prime interest to the coastal decision-makers. A contribution to the preservation and sustainability of the coastal zone constitutes the main aim of this work. Firstly, historical storm tracks and intensities are characterized for the Portuguese coast, in terms of probability of occurrence. Secondly, several storm events with high potential of occurrence are generated using the specific tool DelftDashboard. The hydrodynamic model Delft3D is then used to simulate their effects on currents and on the coastal water levels. Two spatial domains are considered: a large domain encompassing the Iberian coastal zone and a smaller domain for the central region of the Portuguese coast (between cities of Aveiro and Figueira da Foz); this one with a more refined grid. Based on statistical data and by numerical modelling, a review of the impact of coastal storms to different locations within the study area is performed.